RESPONS PERTUMBUHAN VEGETATIF TANAMAN SAWI (Brassica juncea L.) AKIBAT PERLAKUAN MEDIA TANAM DAN DOSIS PUPUK NITROGEN - M. Idris (Jurnal Agroekoteknologi, 2014)
This study aims to get a response mustard plant vegetative growth effect treatment differences planting medium sand and differences of nitrogen fertilizer dosage and combination of both treatments. The research was conducted in the area of vilage Pangkalan Masyhur, altitude 25 m above sea level. The experiment was conducted from August to November 2014. This study used a randomized block design factorial consisting of two factors, namely M1 = Media mixed sandy soil: cow manure (ratio 1: 1), M2 = Media mixed sandy soil: cow manure (ratio 2: 1), M3 = Media mixed sandy soil: cow manure (ratio 3: 1) and the second factor is the dosage of nitrogen fertilizer by 4 levels ie N0 = 0 kg (without fertilizer), N1 = 250 kg ha-1(0.5 g polybag-1), N2 = 500 kg ha-1(1 g polybag-1), N3 = 750 kg ha-11.5 g polybag-1). Parameters observed in this study were plant height (cm), number of leaves, wet weight of each plant of each sample (g), wet weight plant of each polybag (g). The results showed that the planting medium significantly affected plant height, plant wet weight of each plant of each sample and wet weight plant of each polybag, but not significant effect on the amount of leaf mustard. The best result in the treatment of tthe planting medium sand with manure ratio 1 : 1 (M1). Urea dosing effect no significant effect on plant height, number of leaves and mustard plant wet weight of each sample per sample and mustard plant wet weight of each polybag. The combination of growing media and urea effect no significant effect on plant height, number of leaves and mustard plant wet weight of each sample and mustard plant wet weight of each polybag.